Please help me with this math question?? :)The measure of each exterior angle of a regular octogon is _____ the measure of each exterior agle of a regular hexagon.
A. Greater than B. Less than C. Equal to
Answers
now, an OCTAgon, has OCTA=8, sides an HEXAgon, has HEXA=6, sides
check what their external angles are, and compare :)
Can someone simplify this expression? 14y – 5(3 – 2y) and explain how you got it.
Answers
you first expand the brackets so 14y-15-10y then you put the like terms together so you do 14y-10y= 4y 4y-15 which is the answer
14y - 5(3-2y) Distribute what's in the parenthesis 14y- (15+10y) Combine like terms 24y-15
Explain the steps necessary for solving the following equation. x^2-8x-20=0
Answers
First factor the equation (x-10)(x+2) = 0 Then solve for (x-10) and (x+2) x=10 x=-2
(warning: this is quite long :P) the steps are:
Looking at the expression x² +8x-20,we can see that the first coefficient is 1, the second coefficient is 8 and the last term is -20. Now multiply the first coefficient (1) by the last term (-20) to get (1)·(-20)=-20. Now the question is: what two whole numbers multiply to -20 (the previous product). factors of -20: 1,2,4,5,10,20 -1, -2, -4, -5, -10, -20 note: list the negative of each factor. This will allow us to find all possible combinations. These factors pair up to multiply to -20. 1*(-20) = -20 2*(-10) = -20 4*(-5) = -20 (-1)*(20*) = -20 (-2)*(10* = -20 (-4)*(5) = -20 now let's add up each pair of factors to see if one pair adds to the middle coefficient:
From the table above, we can see that the two numbers -2 and 10 multipy to -20 and add up to 8. Now replace the middle term 8x with -2x+10x. Remember, -2 and 10 add up to 8. so this shows us that -2x+10x=8x.
x²+-2x+10x -20 Replace the second term 8x with -2x +10x. (x²-2x)+(10x-20) Group the terms into two pairs. x(x-2x)+(10x-20) Factor out the GCF x from the first group.
x(x-2)+10·(x-2) Factor out 10 from the second group. The goal of this step is to make the terms in the second parenthesis equal to the terms in the first parenthesis.
(x+10)·(x-2) Combine like terms. Or factor out thge common term x-2. ----- ANSWER:
So, x² + 8·x -20 factors to (x+20)·(x-2. In other words, x² + 8·x-20=(x+10)·(x-2)
THIS IS HARD TO UNDERSTAND, BUT HOPE THIS HELPED YOU! AND HOPE YOU GET IT TOO!!! :D
Hope it helps :)
Translate the statement into an equation. Then solve the equation. The sum of 8 and 3 times a number is 23.
Answers
The best way to solve this is to write it out part by part.
The first part is "the sum of 8 and 3," which is (8+3)
The second part is "...times a number," so we have n(8+3)
Lastly, "...is 23," means n(8+3) = 23, so here's the equation. In order to solve for n, divide both sides by (8+3) so 23/(8+3) which is 23/11. So the "number" is 23/11.
Let the number be x 8+3x=23 3x=23-8 3x=15 x=5 The number is 5
(m+2)(m+3)=(m+2)(m-2) what is the answer please
Answers
The first time you look at this, you would think that you can just cancel the (m+2) off of each side. But then you're left with (m+3) = (m-2), and there's no solution for this. So you have to go back and do it the hard way.
Expand each side of the equation. (Clear the parentheses.)